Additive manufacturing in military using - Stankiewicz Grzegorz; Kocur Robert; Kowalski Kazimierz (2023)
The paper presents the current potential of Additive Manufacturing (AM) in the production of devices, replaceable parts, construction infrastructure, medical materials, etc. As part of the presentation of the potential of AM, the currently available technologies and materials used in the implementation of 3D printing were discussed, with particular emphasis on printing technology in metal. The authors reviewed and analyzed the development trends in the use of the above-mentioned of the presented additive manufacturing in technologically leading armies. The analysis of the available information shows that AM in military applications is mainly used in the production of spare parts for "aged" military equipment and for military equipment operated in conditions far away from the sources of supply with "original" technical material means. The paper also presents an original approach to the possibility of using AM in the logistical support of the Polish Armed Forces. The above was based on a holistic analysis of the conditions for the implementation of AM technology in allied armed forces. The paper was completed, with the conclusion that the introduction of AM technology to the logistical support of the Polish Armed Forces will result in an increase in the effectiveness, efficiency and resilience of the supply chain, especially in combat service support.